The Omega System of Global Navigation - Asche, G. P. (The International Hydrographic Review, 2015)
An overview of the Implementation Status of the Omega Navigation System with information on station construction programs and scheduled milestones is presented. The general descriptions of the stations and their new electronic equipments are discussed. Information is also provided on the program for Omega charts and navigational publications required to support the system expansion. Highlights of the concept of international participation and system management are included in this presentation.